The introduction of the Video Assistant Referee supports the fairness of the game - an analysis of the home advantage in the German Bundesliga - Dufner, Anna-Lena; Schütz, Lisa-Marie; Hill, Yannick (Psychology of sport and exercise, 2023)
The introduction of the video assistant referee (VAR) was a landmark in soccer history, yet it is not empirically examined whether the technology contributes to the most supreme value of the game: fair play. Because referees are said to be one driving cause of the home advantage (HA), the aim of this study was to examine whether the HA changed in the German Bundesliga since the implementation of the VAR in the season 2017/18. We examined a total of 2448 games during the four seasons before and after the implementation of the VAR with regards to the game outcomes (i.e., goals and points) as well as indicators of referee bias (i.e., fouls, yellow cards, 2nd yellow cards, red cards, and penalty kicks) for both the home and the away teams. Findings indicate that the VAR influences game outcomes to a fairer degree. Specifically, (i) we found statistical evidence for the HA before, but not after the implementation of the VAR. However, (ii) these results need to be interpreted with caution because direct assessments of the change induced by the introduction of the VAR are not statistically significant. Finally, (iii) with the implementation of the VAR, fewer fouls were committed by both the home and the away team.
Online verfügbar 11. Januar 2023, Artikelversion 27. Januar 2023
Gesehen am 25.05.2023